Distribution and dispersal of the early larval stages of the Japanese spiny lobster Panulirus japonicus in the East China Sea - Taku Yoshimura; Kenji Morinaga; Seiji Oshimo; Yoshinobu Konishi; Tsuneo Goto (New Zealand Journal of Marine and Freshwater Research, 2009)
The annual distribution and dispersal of early‐stage phyllosoma of the Japanese spiny lobster Panulirus japonicus were examined in the East China Sea and the Sea of Japan off western Japan. Early‐stage larvae were sampled mainly in summer and relatively near the coast off western Kyusyu Island. Few larvae were found in the other three seasons in the East China Sea and the Sea of Japan. This finding suggests that P. japonicus larvae are retained in coastal areas for a few months after hatching until stage V and are transported offshore until autumn, before they grow to stage VI. Examination of archival drifter data off western Kyusyu Island during the spawning season of P. japonicus supported the relatively rapid dispersal of the larvae from the East China Sea near Japan to the Pacific Ocean or the Sea of Japan. Larval transport from the East China Sea to the Pacific Ocean, which is considered to be a main distribution area of middle‐ and late‐stage larvae, would occur in the south at approximately 32–33°N in the East China Sea near western Kyusyu Island.